The role of serum lactate in post-cardiac arrest syndrome - Riveiro, Diego; Oliveira, Vanessa Martins de; Brauner, Janete Salles; Vieira, Sílvia Regina Rios (Clinical and Biomedical Research, 2014)
Cardiopulmonary arrest is a medical emergency with significant mortality. The success of resuscitation led to the emergence of post-cardiac arrest syndrome (PCAS), which originates from ischemia-reperfusion injury and its consequent increase in serum lactate. Despite the robust evidence correlating hyperlactatemia as a prognostic marker in critically ill patients, there is insufficient evidence about the role of serum lactate in the outcome of PCAS. Thus, the purpose of this review is to check the current evidence on the role of lactate in predicting mortality in PCAS. Keywords: Cardiac arrest; cardiopulmonary resuscitation; lactic acid